Debt Sustainability in Low-Income Countries : Further Considerations on an Operational Framework and Policy Implications. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper seeks to address queries on several operational issues: (i) the robustness of the indicative thresholds; (ii) modalities for implementing DSAs; and (iii) operational implications for the Fund, Bank, and other international financial institutions and creditors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet